Penanganan Diabetes Sebagai Upaya Mencegah Keparahan COVID-19 - Luse Loe; Ferius Soewito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Coronavirus disease 2019 (COVID-19) is one of the leading health problems globally, including in Indonesia. The first case of COVID-19 in Indonesia was discovered on March 2nd 2020. From then until August 7th 2022, 6.244.978 cases of COVID-19 and 157.095 COVID-19-related death have been recorded. A high virus transmission rate, various clinical manifestations, morbidity and mortality caused by COVID-19 alerts clinician to notice some factors which can make a person vulnerable to COVID-19 and which factors contribute to severe COVID-19. Indonesia’s COVID-19 case fatality rate (CFR) is higher than the global CFR. COVID-19 mortality in Indonesia mainly occurs in patients with comorbidity, of which the most common is diabetes mellitus.